2015
DOI: 10.1016/j.coal.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced microbial coalbed methane generation: A review of research, commercial activity, and remaining challenges

Abstract: Made available through Montana State University's ScholarWorks scholarworks.montana.edu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
145
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(145 citation statements)
references
References 110 publications
0
145
0
Order By: Relevance
“…Gilcrease and Shurr (2007) had emphasized the necessity of yeast extract in the context of coal dependent methanogenesis for successful in situ application of microbial enhanced CBM. Also, several companies, including Luca Technologies, Inc., and Ciris Energy, whose primary objective was to stimulate microbial enhanced CBM production in CBM wells through adding nutrients have commercially used yeast extract in their amendment mixture as a multinutrient (Ritter et al, 2015). Though, there are differences in the media used to investigate methane production in this study and the oligotrophic, higher-pressure in situ environment.…”
Section: Salinity (%Nacl)mentioning
confidence: 87%
See 2 more Smart Citations
“…Gilcrease and Shurr (2007) had emphasized the necessity of yeast extract in the context of coal dependent methanogenesis for successful in situ application of microbial enhanced CBM. Also, several companies, including Luca Technologies, Inc., and Ciris Energy, whose primary objective was to stimulate microbial enhanced CBM production in CBM wells through adding nutrients have commercially used yeast extract in their amendment mixture as a multinutrient (Ritter et al, 2015). Though, there are differences in the media used to investigate methane production in this study and the oligotrophic, higher-pressure in situ environment.…”
Section: Salinity (%Nacl)mentioning
confidence: 87%
“…However, according to the recent review by Ritter et al (2015), the measurements of microbial populations from the pilot study of Luca Technologies indicated that they were successful in maintaining desirable microbial community in situ in response to the nutrient amendment. Thus, stimulation or augmentation along with nutrient medium, as also developed in this study, can help in the growth of enriched microbes inside the coal seams, countering competition.…”
Section: Salinity (%Nacl)mentioning
confidence: 95%
See 1 more Smart Citation
“…Coalbed methane (CBM) is one of the most important and potential energies which has been recognized as an alternative to oil and has achieved more and more attention in recent years [1]. Different with the conventional natural gas, a coal seam is both a resource and reservoir of CBM and stores methane in nanopores in the form of adsorption, resulting in the low recovery of CBM exploitation [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, coal is heterogeneous and hydrophobic in characteristics, which makes it recalcitrant to common microbial degradation5. Traditionally, two main approaches may be deployed to enhance the production of CBNG, i.e., bio-stimulation and bio-augmentation [12,13]. Bio-stimulation is to stimulate indigenous microbial growth by adding supplement compounds and nutrients while bio-augmentation is to add external microbial consortia [5,12].…”
mentioning
confidence: 99%